Structural health monitoring : research and applications : peer reviewed papers from the 4th Asia-Pacific workshop on structural health monitoring, December 5-7, 2012, Melbourne, Australia - Chiu, W. K.; Galea, S. C. (Trans Tech Publication, 2013)
Structural health monitoring has international relevance across maritime, aerospace and infrastructure domains for both civilian and military end-users. The aim of this book is to collect the most recent developments and research knowledge on this topic, with focusing in particular on the Asia-Pacific region. The collection covers 54 peer reviewed papers covering up-to-date research results in structural health monitoring. Fifty-six papers from the December 2012 workshop present new developments in monitoring aircraft structure conditions, civil structures, wind turbines, pipelines, and buildi.
Keywords: Structural health monitoring -- Congresses.; Structural analysis (Engineering) -- Congresses.; elektronické knihy; electronic books